The Relationship between Family Support for Elderly and Visits to The Integrated Service Post in The Working Area of Waena Health Center, Jayapura City - Makaba, Merry Yanti; Medyati, Novita; Makaba, Sarce (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study focuses on discussing the relationship of family support for the elderly to visit the elderly posyandu [Integrated Service Post] in the Waena Health Center working area of Jayapura City, Papua Province. This type of research is a cross-sectional study on the elderly population in 4 Posyandu in the Waena Health Center working area as many as 356 elderly with a sample size of 78 elderly people conducted in December 2023-January 2024. Data was obtained using a questionnaire and analyzed using chi square and binary logistic regression. The results obtained factors that have a significant relationship in the elderly to the visit of the Elderly Posyandu in the Waena Health Center Working Area, Jayapura City, Papua Province emotional support (p value 0.003; RP=1.864 CI 95% (2.04-45.386), instrumental support (p value 0.000; RP=2.64 CI95% (1.54-4.52), informational support (p value 0.000; RP=2.249 CI95% (1.593-3.175) while appreciation support is not significant in the elderly to the Elderly Posyandu visit (p value 0.089; RP=1.671 CI 95% (0.91-3.07). The dominant factor of family support in the elderly on the elderly posyandu visit is instrumental support (p value 0.000; OR=9.2; CI95% (3.247 - 26.068).